N.B. Papadopoulou (ed.), Molottis. Archaeological Atlas of the ancient settlements in the municipal region of Ioannina. - Dickinson , Oliver (Journal of Greek Archaeology, 2024)
This book is effectively a gazetteer of ancient sites in the municipal area of Ioannina, which was the centre of the territory of the Molossoi (in some later sources Molottoi), a landlocked people who were the most prominent among the tribal groups of Epirus in Classical antiquity; their territory extended to include the famous oracle of Zeus at Dodona by historical times. It is a collaborative work by many archaeologists working at the Ephorate of Ioannina, aiming to shed light on this poorly known region, and is entirely in Greek. It covers both excavated sites and those identified in various ways, often simply by the appearance of some casual find, from remote prehistory (there are some well-known Palaeolithic sites) to the end of the Roman period.